(untitled) (Modern information system and technologies, 2018)
Now, the topic of web application development is especially popular, as more and more electronic services work through remote online resources, most companies provide on-line services and services, as well as more and more diverse applications on different operating systems developed specifically with the use of the web-interfaces, thus displacing the application programming and developing web programming.